FORMATION OF PRAGMATIC COMPETENCE IN HIGH SCHOOL STUDENTS - Арделян, Олена; Юрчик, Аліна (SWorldJournal, 2025)
Pragmatic competence in the process of teaching English occupies an extremely important place, since it is it that ensures the ability of students to interact effectively in real communicative situations. The formation of pragmatic competence requires the